Immune-related hepatitis and hypophysitis are associated with superior survival in melanoma patients treated with combined ipilimumab and nivolumab - Hifaa Al Remawi; Maria Lindén; Zhiyuan Zhao; Ankur Pandita; Anna Rudin; Lars Ny; Sara Bjursten; Max Levin (OncoImmunology)
Combination CTLA-4 (ipilimumab) and PD-1 (nivolumab) checkpoint inhibition (dual-ICI) improves survival in patients with advanced melanoma. However, many patients also experience immune-related adverse events (irAE) that require systemic treatment with corticosteroids. Corticosteroids dampen the anti-tumoral response and may impair survival. Here, we investigated the association between irAE and overall survival as well as exposure to corticosteroids and second line immunosuppressants in dual ICI-treated patients with advanced melanoma (n = 205). Patients with irAE (n = 113) had superior OS compared to patients with no irAE (n = 92). The survival benefit persisted after adjusting for immortal time bias. Regarding specific irAE, patients with colitis, hepatitis, rheumatic irAE, hypophysitis, and skin-related irAE had improved OS after adjusting for negative baseline factors. A survival benefit persisted for hypophysitis (p = 0.03) and hepatitis (p = 0.04) after adjusting for immortal time bias, whereas rheumatic (p = 0.05) and skin-related irAE (p = 0.06) where borderline significant. Hepatitis and colitis required higher doses of corticosteroids for longer times and more often second-line immunosuppression compared to other irAE. In conclusion, irAE are associated with superior OS in patients with advanced melanoma treated with dual ICI. Hepatitis and hypophysitis were most strongly associated with better survival outcomes. Studies investigating the mechanisms underlying hepatitis and hypophysitis may identify important response mechanisms.